SOME INEQUALITIES OF THE HERMITE HADAMARD TYPE FOR PRODUCT OF TWO FUNCTIONS - Nguyen Ngoc Hue; Duong Quoc Huy (Journal of New Theory)
Abstaract−In this paper, we shall establish some new inequalities of the Hermite Hadamard type for product of two functions to belong to the class of s-convex functions and the class of h-convex functions. Some results of product of two functions that belong to two classes of different functions are also given